The phylogenetic relationships of basal archosauromorphs, with an emphasis on the systematics of proterosuchian archosauriforms - Ezcurra, Martin Daniel (2016)
The early evolution of archosauromorphs during the Permo-Triassic constitutes an excellent empirical case study to shed light on evolutionary radiations in deep time and the timing and processes of recovery of terrestrial faunas after a mass extinction. However, macroevolutionary studies of early archosauromorphs are currently limited by poor knowledge of their phylogenetic relationships. In particular, one of the main early archosauromorph groups that need an exhaustive phylogenetic study is “Proterosuchia,” which as historically conceived includes members of both Proterosuchidae and Erythrosuchidae. A new data matrix composed of 96 separate taxa (several of them not included in a quantitative phylogenetic analysis before) and 600 osteological characters was assembled and analysed to generate a comprehensive higher-level phylogenetic hypothesis of basal archosauromorphs and shed light on the species-level interrelationships of taxa historically identified as proterosuchian archosauriforms. The results of the analysis using maximum parsimony include a polyphyletic “Prolacertiformes” and “Protorosauria,” in which the Permian Aenigmastropheus and Protorosaurus are the most basal archosauromorphs. The enigmatic choristoderans are either found as the sister-taxa of all other lepidosauromorphs or archosauromorphs, but consistently placed within Sauria. Prolacertids, rhynchosaurs, allokotosaurians and tanystropheids are the major successive sister clades of Archosauriformes. The Early Triassic Tasmaniosaurus is recovered as the sister-taxon of Archosauriformes. Proterosuchidae is unambiguosly restricted to five species that occur immediately after and before the Permo-Triassic boundary, thus implying that they are a short-lived “disaster” clade. Erythrosuchidae is composed of eight nominal species that occur during the Early and Middle Triassic. “Proterosuchia” is polyphyletic, in which erythrosuchids are more closely related to Euparkeria and more crownward archosauriforms than to proterosuchids, and several species are found widespread along the archosauromorph tree, some being nested within Archosauria (e.g., “Chasmatosaurus ultimus,” Youngosuchus). Doswelliids and proterochampsids are recovered as more closely related to each other than to other archosauromorphs, forming a large clade (Proterochampsia) of semi-aquatic to aquatic forms that includes the bizarre genus Vancleavea. Euparkeria is one of the sister-taxa of the clade composed of proterochampsians and archosaurs. The putative Indian archosaur Yarasuchus is recovered in a polytomy with Euparkeria and more crownward archosauriforms, and as more closely related to the Russian Dongusuchus than to other species. Phytosaurs are recovered as the sister-taxa of all other pseudosuchians, thus being nested within Archosauria.